Problematika Pendidikan Agama Di Madrasah - Khoirun Niswah; Dwi Noviani; Paizaluddin Paizaluddin (STIKes Ibnu Sina Ajibarang, 2023)
Madrasah is one of the Islamic educational institutions in Indonesia has a big enough contribution in shaping the character, personality and noble character. The existence of madrasas in the current global era is very important in the future to participate in building and solving multidimensional crises that is being experienced by our nation Indonesia. Therefore madrasas in hope that in the future it can prepare its students to become the next generation of the nation who have good religious knowledge and have a high knowledge of science and technology. Because with provision of good religion and science and technology, the future is expected of our nation will soon emerge from some multidimensional crisis. And finally it will towards a country that is just and prosperous and a prosperous nation highly civilized and respected by other countries.But the current reality of madrasas is still very concerning. Interest from the community to send their children to madrasas is still low. Besides that, the support from the government also received less portion same as public schools. In the future if we all realize that the existence of madrasas is still very much needed to form humans those who believe in doing good deeds and have knowledge and technology must do so supported by all levels of society, starting from the Muslims, institutions. Islamic education, Ministry of Religion and government policy.